On the Absence of ‘Fragrant Film’: Changing Images of the Author in Indonesia - Meghan Downes (Al-Jami'ah Research Centre, 2013)
A more varied and plural image of ‘the author’ has emerged during the past decade, brought about by subsequent literary trends including Islamic women’s writing and ‘teen-lit’ written by and for teenagers. ‘sastra wangi’ (fragrant literature) was a popular media label used to describe the controversial work of young female authors writing during the early ‘reformasi’ period. One decade on, we are seeing film adaptations of such work, none of which have provoked a comparable level of furore. The absence of any kind of ‘fragrant film’ discourse denigrating the femininity of the narratives reveals a shift in public discourse around authorship in contemporary Indonesia. This article uses close textual readings, media discourse analysis and ethnographic audience research to examine the relationship between such trends, and the ways in which young Indonesians engage with popular narratives.[Munculnya penulis-penulis muda pada beberapa dekade terakhir di Indonesia dengan beragam citra masing-masing telah mendorong lahirnya tren baru dalam dunia sastra, termasuk tulisan-tulisan muslimah dan sastra remaja yang ditulis oleh dan untuk remaja. Tren tersebut salah satunya memunculkan apa yang kemudian populer dengan istilah ‘sastra wangi’, istilah yang digunakan untuk menyebut karya-karya sastra yang memicu kontroversi dan ditulis oleh penulis perempuan pada masa awal era reformasi. Pada satu dekade berikutnya, beberapa karya sastra tersebut diadaptasi dalam bentuk film. Namun demikian, film yang diproduksi tidak memicu kontrovesi, tidak seperti halnya ketika karya sastra itu pertama kali ditulis. Absennya perdebatan dan kecaman terhadap ‘film wangi’ mengindikasikan pergeseran dalam perdebatan publik mengenai ‘kepengarangan’ di Indonesia kontemporer. Artikel ini didasarkan pada pembacaan tekstual, analisis wacana media, dan riset audien secara etnografis untuk mengungkap hubungan antara tren-tren sastra di atas dan bagaimana sikap anak muda Indonesia terhadap sastra-sastra populer tersebut.]